Aplicação do efeito seebeck na conversão da energia térmica em elétrica - Carvalho Neto, José Barroso de (Universidade Federal Rural do Semi-Árido, 2018)
Thermocouples are electrical appliances of considerable applicability in industry, whose main characteristics are durability and sensitivity to temperature, their operation is based on the thermoelectric phenomenon known as Seebeck Effect, in that when joining one of the ends of a pair of conductive wires and subjecting a temperature difference between the ends results in a thermoelectric potential difference. The objective of this study is to analyze the development and operation of a system of conversion of thermal energy to electric from the Seebeck Effect. For this, quantitative tests were carried out with the purpose of verifying the generated electric voltage values for a series association in which a limited amount of type K thermocouples was used. The research method used for the experimental design was the performance of tests for analysis and calculation of the results. The conclusive elements point out that the tests performed were satisfactory, since the generated voltage value exceeded the expected standards for such a configuration, being thus verified the real veracity of the researched effect and total effectiveness of the study objective.
Monografia
Keywords: Termopares; Seebeck; Energia; Tensão; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA